Numerical Simulations of Flow Behaviour in Driven Cavities at High Reynolds Numbers - FUDHAIL ABDUL MUNIR, F.A Munir; MOHD RODY MOHD ZIN, M.R.M Zin; NOR AZWADI CHE SIDIK, N.A.C Sidik; MOHD IRWAN MOHD AZMI, M.I.M Azmi (International Islamic University Malaysia, 2012)
In recent years, due to rapidly increasing computational power, computational methods have become the essential tools to conduct researchers in various engineering fields. In parallel to the development of ultra high speed digital computers, computational fluid dynamics (CFD) has become the new third approach apart form theory and experiment in the philosophical study and development of fluid dynamics. Lattice Boltzmann Method (LBM) is an alternative method to conventional CFD. LBM is relatively new approach that uses simple microscopic models to simulate complicated microscopic behaviour of tramsport phenomena. In this paper, fluid flow behaviours of steady incompressible flow inside lid driven square cavity are studied. Numerical calculations are conducted for different Reynolds numbers by using Lattice Boltzmann scheme. The objective of the paper is to demonstrate the capability of this Lattice Boltzmann scheme for engieering applications particularly in fluid transport phenomena.